(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
This paper presents the case of a 26-year-old hotel management student who accidentally suffocated and died while practicing autoerotic asphyxia. The findings suggested that his death was accidental and due to asphyxia by suffocation performed to enhance sexual gratification during masturbation.